The Effect of Chicken Manure and Lime (CaCO3) towards a Number of Soil Chemical Properties and the Growth of Corn (Zea mays L.) at Kwala Bekala Inceptisol - eko tampubolon; MMB DAMANIK; Purba Marpaung (Jurnal Agroekoteknologi, 2018)
A pot trial at the screen house of College of Agriculture, University of North Sumatera was carried out to evaluate the effects of varied levels of chicken manure and lime of CaCO3 towards a number of soil chemical properties and corn growth on Inceptisol of Kwala Bekala. The trial was 3 x 3 factorial arranged in a randomized complete block design. Treatments included three levels of chicken manure: 0, 5 and 10 t/ha and three levels of lime and three replications to meet 27 experimental units, respectively. The results showed that 10 t/ha of chicken manure significantly increased the availability of phosphorus in soil and also the absorption of phosphorus by plants. The results also showed that at 4.47 t/ha lime of CaCO3 significantly increased the soil pH. However, there was no interaction effect between chicken manure and lime of CaCO3. Keywords: chicken manure, corn growth, Inceptisol, lime of CaCO3